Analisis Kinerja Pemerintah Distrik Kembu, Kabupaten Tolikara, Provinsi Papua Pegunungan - Wenda, Yani; Rares, Joyce Jacinta; Kimbal, Alfon (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to examine and explain the performance of the government in implementing regional autonomy affairs in Kembu District, Tolikara Regency. The data used in this research are primary data obtained from direct interviews with respondents. The data analysis technique employed is an interactive model of qualitative data analysis. The results of the study indicate that, in terms of productivity, the implementation of programs is considered fairly good, as evidenced by the achievement of the planned objectives. However, the efficiency in the use of resources remains suboptimal, particularly regarding budget absorption, the utilization of facilities and infrastructure, and the optimization of human resources among government officials. The government’s responsiveness to community needs is generally good, with work programs largely aligned with the actual conditions and issues in the district area. The government also demonstrates a reasonable level of responsiveness to community aspirations and environmental changes. In terms of accountability, the implementation of programs and policies has been carried out transparently and is accountable, as reflected in the preparation of the annual performance report (LAKIP). Nevertheless, leadership roles and institutional systems still need to be strengthened to support overall performance improvement.